Learning Outcomes for Academic programs at the University of Aden: Reality and Expectations Desired from the Standpoint of Deans, Heads of Academic Departments, the Faculty Members and Students Expected to Graduate - Altaf Ramadhan Ibrahim (University of Science and Technology, Yemen, 2014)
Learning outcomes for academic programs at the University of Aden: reality and expectations desired from the standpoint of deans, heads of academic departments, the faculty members and students expected to graduate ABSTRACT This study aims to evaluate the status and the possibility of the development of learning outcomes in academic programs of the faculties of the University of Aden. Such an evaluation was conducted in terms of meeting the needs of learners and how to achieve their creativity and  ability to connect their experience with  the world outside educational  institutions. The evaluation for the in academic programs was from the point of views of the deans of the faculties, vice deans, heads of academic departments,  staff, and expected  graduate students in the academic year of 2009-2010. The study sample consisted of 123 persons, including (8) deans,  (14) vice-dean,  (14) Head of Department, (16) faculty member, and (71) expected graduate students. The researcher adopted a descriptive approach to identify the point of views of the study sample  related to status and the possibility of development learning outcomes, that are meeting the learners' needs and how to achieve their creativity and  ability to consist with the requirements of the labor market. To achieve the study objectives, a questionnaire consists of 40 items was developed. Items were distributed in two main fields: (1) The status of learning outcomes and the possibility of initiating  learning outcomes that are meeting the needs of the learner and achieve their creations. (2) The status of learning experiences and the possibility of embarking the development of learning experiences to help connect the student in the world outside the institution. The questionnaire validity was assured using the chi square to examine the significant differences in the degree of approval of the experts that was not less than about 91% on all items. also used Chronbakh Alpha  equation to calculate its reliability, which was reached to (0.89). The study came up with results showed that the learning outcomes development in many academic programs are not meeting the needs of learners or helping them to achieve any of their creativities. The weighted mean of such development was (0.39) with a SD of (13.1). A marked decline in the level of development of learning experiences help connect the student in the world outside of the educational institution . Learning outcomes were not consistent with labor market requirements. The mean of such level was (0.45) with a SD of (14.2). In contrast, results revealed a relatively high level that reflect the possibility of initiating the development of learning outcomes are meeting learners needs, and helping them  to achieve their creations, The mean of such level was (68%) with a SD of (16.7). In addition,  the level of  possibility to initiate  learning experiences development to meet labor market requirements was high. Its mean was (0.75) with a SD of (15.7).